Cost-effectiveness analysis of serplulimab combination therapy versus chemotherapy alone for patients with extensive-stage small cell lung cancer - Zheng, Zhiwei; Chen, Hongcai; Cai, Hongfu (Frontiers in Oncology, 2024)
Background:Serplulimab has shown promising results in the treatment of extensive-stage small cell lung cancer (ES-SCLC). This study aimed to evaluate the cost-effectiveness of serplulimab combination therapy compared to chemotherapy alone in patients with ES-SCLC from the Chinese healthcare system perspective.Methods: A partitioned survival model was developed to simulate the costs and outcomes of patients receiving serplulimab combination therapy or chemotherapy alone over a time horizon of 10 years. Data on overall survival, progression-free survival, and adverse events were obtained from the ASTRUM-005 randomized clinical trial. Costs were estimated from a healthcare system perspective and included drug acquisition, administration, monitoring, and management of adverse events.One-way and probabilistic sensitivity analyses were conducted to assess the impact of uncertainty on the results.The base-case analysis showed that the combination of serplulimab and chemotherapy has demonstrated a significant increase in QALYs of 0.626 compared to chemotherapy alone. This improved outcome is accompanied by an additional cost of $10893.995. The ICER for incorporating serplulimab into the treatment regimen is $17402.548 per QALY gained. One-way sensitivity analysis confirmed the robustness of the findings. Probabilistic sensitivity analysis demonstrated that serplulimab combination therapy had a 97.40% high probability of being cost-effective compared to chemotherapy alone at the WTP thresholds.In contrast to chemotherapy as a standalone treatment, the addition of serplulimab to chemotherapy is believed to offer potential cost-effectiveness as a preferred initial therapeutic approach for patients with ES-SCLC in China.